Agriculture 4.0 in Hungary the challenges of 4th industrial revolution in Hungarian agriculture within the frameworks of the common agricultural policy - Somosi Sarolta; Számfira Gabriella; Central European PhD Workshop on Technological Change and Development Szeged 2019. április (Faculty of Economics and Business Administration Doctoral School in Economics Szeged, 2020)
The impacts of the 4th industrial revolution, which is considered a “general purpose technology”, do not appear only in the manufacturing sector or in the increasingly ICTintensive services sector. Agriculture, which is using manufactured inputs in more and more automatized factories, and which relies highly on technology in its basic activities, has also been going through remarkable changes recently. Precision farming (1), optimized usage of scarce inputs (2) and so attaining a more economy and ecology-friendly (sustainable) farming system (3) are all potential positive outcomes of the technological development of Industry 4.0 taking place in agriculture. In connection with this topic, our main aim is to determine the position of Hungary in this field, and whether there are any obstacles in this process. Both in the theoretical and empirical research conducted, we focus on the agricultural workforce, whether it is ready to keep pace with developments or if Hungarian farmers may be facing difficulties. Finally, as an outlook we examine the European Union's Common Agricultural Policy and its future changes, if it is currently or close to handling this challenge?
Keywords: Társadalomtudományok; Politikatudomány